2016
DOI: 10.1371/journal.pone.0167120
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous Immunoglobulin Combined with Corticosteroid on the Progression of Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis: A Meta-Analysis

Abstract: BackgroundIntravenous immunoglobulin (IVIG) treatment is commonly used to treat Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) with controversial therapeutic effect.MethodsWe conducted a comprehensive meta-analysis through combining the published eligible studies to evaluate the effectiveness of IVIG on SJS and TEN treatment.ResultsA total of 26 studies were selected from public available databases. The combination of IVIG and corticosteroid markedly reduced the recovery time (by 1.63 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 63 publications
2
21
0
7
Order By: Relevance
“…Case series and a systematic review suggest that IVIG, particularly high-dose IVIG (>2 g/kg total dose), improves survival (Campione et al, 2003;Huang et al, 2012;Prins et al, 2003;Trent et al, 2003;Viard et al, 1998), but other reviews, and the 281-patient Euro-SCAR cohort, showed no mortality benefit (Faye and Roujeau, 2005;Firoz et al, 2012;Lee et al, 2013;Schneck et al, 2008;Zimmermann et al, 2017). Some studies have suggested improved outcomes in those receiving both corticosteroids and IVIG (Chen et al, 2010;Yang et al, 2009;Ye et al, 2016). Although the ability to draw definitive conclusions from our data is limited, those receiving both agents in this cohort had the lowest standardized mortality ratio (0.52; 95% CI ¼ 0.21e0.79) of any treatment group, suggesting a reason for further study of combination corticosteroids and IVIG as a therapeutic option for SJS/TEN.…”
Section: Discussionmentioning
confidence: 99%
“…Case series and a systematic review suggest that IVIG, particularly high-dose IVIG (>2 g/kg total dose), improves survival (Campione et al, 2003;Huang et al, 2012;Prins et al, 2003;Trent et al, 2003;Viard et al, 1998), but other reviews, and the 281-patient Euro-SCAR cohort, showed no mortality benefit (Faye and Roujeau, 2005;Firoz et al, 2012;Lee et al, 2013;Schneck et al, 2008;Zimmermann et al, 2017). Some studies have suggested improved outcomes in those receiving both corticosteroids and IVIG (Chen et al, 2010;Yang et al, 2009;Ye et al, 2016). Although the ability to draw definitive conclusions from our data is limited, those receiving both agents in this cohort had the lowest standardized mortality ratio (0.52; 95% CI ¼ 0.21e0.79) of any treatment group, suggesting a reason for further study of combination corticosteroids and IVIG as a therapeutic option for SJS/TEN.…”
Section: Discussionmentioning
confidence: 99%
“…Because few were treated with IVIG, therefore we cannot assess the treatment outcome of IVIG to be positive or negative. However, there were studies documenting the favourable outcome of IVIG either alone or combined with SCS in slowing the disease progression among SJS/TEN patients [23, 33, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that the use of cyclosporin in patients with SJS and TEM was associated with decreased mortality (Kirchhof et al, 2014). One systematic review with metaanalysis suggested that intravenous immunoglobulin combined with corticosteroid may reduce the recovery time of patients with SJS and TEN, mainly among Asians (Ye et al, 2016).…”
Section: Discussionmentioning
confidence: 99%